Acrylate-based materials for heart valve scaffold engineering. (17th November 2017) - Santoro, Rosaria; Venkateswaran, Seshasailam; Amadeo, Francesco; Zhang, Rong; Brioschi, Maura; Callanan, Anthony; Agrifoglio, Marco; Banfi, Cristina; Bradley, Mark; Pesce, Maurizio
Abstract : In the present contribution we describe new acrylates materials for valve scaffold engineering, based on a high throughput screen. Abstract : Calcific aortic valve disease (CAVD) is the most frequent cardiac valve pathology. Its standard treatment consists of surgical replacement either with mechanical (metal made) or biological (animal tissue made) valve prostheses, both of which have glaring deficiencies. In the search for novel materials to manufacture artificial valve tissue, we have conducted a high-throughput screening with subsequent up-scaling to identify non-degradable polymer substrates that promote valve interstitial cells (VICs) adherence/growth and, at the same time, prevent their evolution toward a pro-calcific phenotype. Here, we provide evidence that one of the two identified 'hit' polymers, poly(methoxyethylmethacrylate- co -diethylaminoethylmethacrylate), provided robust VICs adhesion and maintained the healthy VICs phenotype without inducing pro-osteogenic differentiation. This ability was also maintained when the polymer was used to coat a non-woven poly-caprolactone (PCL) scaffold using a novel solvent coating procedure, followed by bioreactor-assisted VICs seeding. Since we observed that VICs had an increased secretion of the elastin-maturing component MFAP4 in addition to other valve-specific extracellular matrix components, we conclude that valve implants constructed with this polyacrylate will drive the biological response of human valve-specific cells.